1995
DOI: 10.1016/0304-3959(94)00228-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-3-glucuronide: evidence to support its putative role in the development of tolerance to the antinociceptive effects of morphine in the rat

Abstract: Antinociceptive tolerance to morphine (MOR) was induced in groups of Sprague-Dawley rats receiving continuous intravenous infusions of morphine sulphate administered by 3 different MOR dosing regimes. At appropriate intervals throughout each infusion period, antinociceptive testing was performed using the tail-flick latency test and blood samples were collected. Groups of saline (SAL)-infused control rats also underwent antinociceptive testing and blood sample collection. Complete antinociceptive tolerance dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(33 citation statements)
references
References 43 publications
2
30
0
1
Order By: Relevance
“…These results were in accordance with those reported by Smith and Smith [30] who found that antinociceptive tolerance to MOR was induced in groups of Sprague-Dawley rats receiving continuous intravenous infusion of MOR, and it was related to the plasma concentration ratio of M3G and MOR. Also, in this study in the comparison of plasma concentrations in patients with VAS pain scores of adequate (VAS B 15 mm) or inadequate (VAS [ 15 mm) pain relief, a simple relationship between plasma concentrations of M3G, M3G/MOR and clinical effect was identified and this correlation was highly significant with M3G/MOR.…”
Section: Discussionsupporting
confidence: 94%
“…These results were in accordance with those reported by Smith and Smith [30] who found that antinociceptive tolerance to MOR was induced in groups of Sprague-Dawley rats receiving continuous intravenous infusion of MOR, and it was related to the plasma concentration ratio of M3G and MOR. Also, in this study in the comparison of plasma concentrations in patients with VAS pain scores of adequate (VAS B 15 mm) or inadequate (VAS [ 15 mm) pain relief, a simple relationship between plasma concentrations of M3G, M3G/MOR and clinical effect was identified and this correlation was highly significant with M3G/MOR.…”
Section: Discussionsupporting
confidence: 94%
“…M3G binds to microglial TLR4 to produce hyperalgesia and allodynia (pain response from non-noxious stimuli) (Due et al, 2012), whereas M6G binds to MOR to produce potent pain inhibition (Wittwer and Kern, 2006; see Figure 3). Pharmacological studies show that administration of M3G correlates with nociception (Smith and Smith, 1995) and that M3G actively opposes opioid analgesia, as well as the analgesic effects of M6G (Ekblom et al., 1993; Roeckel et al, 2017;Doyle and Murphy, 2018). …”
Section: Morphine Metabolismmentioning
confidence: 99%
“…In this scenario, time-dependent M3G accumulation could be responsible for the appearance of morphine tolerance. For example, Smith and Smith (22) observed an inverse relationship between morphine-associated antinociception and M3G concentrations. However, careful examination of the influence of M3G pretreatment on morphine antinociception in rats revealed that acute M3G exposure, at concentrations similar to those produced by pharmacologically-relevant doses of morphine, does not attenuate antinociception to a significant extent (23,24).…”
Section: Metabolite Contributions To Opioid Response and Tolerancementioning
confidence: 99%